2021
DOI: 10.5380/rf.v51i2.69403
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF THERMAL MODIFICATION ON THE PHYSICAL AND MECHANICAL PROPERTIES OF Eucalyptus badjensis MIXED PARTICLEBOARD / OSB PANELS

Abstract: The objective of this research was to evaluate the effects of thermal modifications, at different temperatures and exposure times, on the technological properties of mixed particleboard / OSB panels made out of Eucalyptus badjensis. Using the wood of Eucalyptus badjensis, Particleboard, OSB and mixed Particleboard/OSB panels (control and thermally modified) were manufactured. The mixed panels’ thermal modification was carried out under three temperatures (180ºC, 200ºC and 220ºC) and two exposure times (10 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
1
1
Order By: Relevance
“…Thus, comparing the present study with the one conducted by Pereira et al [58], it is understood that the differences found in the results obtained between the research are related to the longer time of exposure to temperature during thermal modification. This is in line with what Sinha, Gupta and Nairn obtained [60], who found that heat treatment of OSB caused a significant reduction in flexural strength and stiffness, with the greatest reduction occurring at 200 • C for 2 h compared to the other conditions evaluated (reference, 100 • C at 1 and 2 h, and 200 • C at 1 h exposure).…”
Section: Mechanical Evaluationscontrasting
confidence: 49%
See 1 more Smart Citation
“…Thus, comparing the present study with the one conducted by Pereira et al [58], it is understood that the differences found in the results obtained between the research are related to the longer time of exposure to temperature during thermal modification. This is in line with what Sinha, Gupta and Nairn obtained [60], who found that heat treatment of OSB caused a significant reduction in flexural strength and stiffness, with the greatest reduction occurring at 200 • C for 2 h compared to the other conditions evaluated (reference, 100 • C at 1 and 2 h, and 200 • C at 1 h exposure).…”
Section: Mechanical Evaluationscontrasting
confidence: 49%
“…In their paper, Pereira et al [58] who also studied the thermal treatment (at 180 • C, 200 • C and 220 • C) in two exposure times (10 and 12 min) in particleboard and OSB produced with eucalyptus wood and phenolic resin, it was concluded that the thermal modification at the exposure times and temperatures studied did not influence the results of the mechanical properties of the panels.…”
Section: Mechanical Evaluationsmentioning
confidence: 97%